Holorchis gigas n. sp. (Digenea: Lepocreadiidae) from the yellow-striped sweet-lips Plectorhinchus chrysotaenia (Perciformes: Haemulidae) from Lizard Island, Great Barrier Reef, with observations on Aephnidiogenes major - Bray, Rodney A.; Cribb, Thomas H. (Zootaxa, 2007)
Holorchis gigas n. sp. is described from the fish Plectorhinchus chrysotaenia off Lizard Island on the Great Barrier Reef. It grows to over 180mm and is, therefore, much larger than any previously described species. It also differs from other Holorchis spp. in combinations of a different cirrus-sac structure, widely separated testes, entire ovary, short post-testicular region and the vitellarium not reaching the ventral sucker. Aephnidiogenes major is reported from Diagramma labiosum off Lizard and Heron Islands and P. chrysotaenia, off Lizard Island. Measurements of A. major are given.